Quantitative evaluation of the development of isoprenaline-induced heart lesions - Mráz, M; Faltová, E; Sedivý, J; Protivová, L; Pilný, J (Physiologia Bohemoslovaca, 1980)
The development of heart lesions induced by isoprenaline (ISO) was quantitatively evaluated by 203Hg-Mercurascan (MSC) which was taken up and retained in the damaged cells. After the administration of ISO, the MSC uptake increased immediately at a constant rate, which was independent of the dose of ISO. A higher cardiotoxic effect of increased doses of ISO was caused by prolongation of the time during which the development of heart lesions proceeded. Later, when the damaged cells were subjected to cytolysis, MSC uptake decreased. The blockade of the effect of ISO by methypranol immediately stopped any further increase of MSC uptake. The accumulation of other labelled substances (Neohydrin, HgCl2, CaCl2) in the damaged myocardium was compared with the uptake of MSC. MSC and HgCl2 in particular are suitable for the observation of early changes; relatively less CaCl2 accumulated in the damaged hearts, but it can be used for the detection of more advanced lesions.
Keywords: kardiomyopatie; isoprenalin; Male; Rats; Isoproterenol; myokard; Myocardium; Cardiomyopathies; krysa rodu Rattus; Mercury Radioisotopes; mužské pohlaví; radioizotopy rtuti; Animals; zvířata